2011
DOI: 10.1007/s00259-011-1748-6
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT leads to the detection of metastatic involvement of the heart in non-Hodgkin’s lymphoma

Abstract: We describe two rare cardiac findings on baseline FDG PET in histologically proven aggressive large B-cell non-Hodgkin's lymphoma (NHL).The first case is a 21-year-old woman with stage IV NHL with a superior mediastinal mass and two lung nodules on contrast-enhanced CT images. FDG PET/CT showed intense uptake in these lesions and, without contiguity, a round pathological cardiac uptake in the apical septum and the right ventricle (a, b FDG PET images; c, d fusion FDG PET/CT images; transverse and sagittal, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…The involvement is usually revealed by cardiac complications and is associated with a poor prognosis [21,22]. Few cases of cardiac involvement in NHL have been reported, both primary and metastatic, detected by 18 F-FDG PET-CT [9][10][11]. Julian et al reported two cases of NHL with cardiac involvement (apical septum, right ventricle and right auricle) detected by 18 F-FDG PET-CT that allowed an early diagnosis and chemotherapy, therefore, improving the survival [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement is usually revealed by cardiac complications and is associated with a poor prognosis [21,22]. Few cases of cardiac involvement in NHL have been reported, both primary and metastatic, detected by 18 F-FDG PET-CT [9][10][11]. Julian et al reported two cases of NHL with cardiac involvement (apical septum, right ventricle and right auricle) detected by 18 F-FDG PET-CT that allowed an early diagnosis and chemotherapy, therefore, improving the survival [9].…”
Section: Discussionmentioning
confidence: 99%
“…Few cases of cardiac involvement in NHL have been reported, both primary and metastatic, detected by 18 F-FDG PET-CT [9][10][11]. Julian et al reported two cases of NHL with cardiac involvement (apical septum, right ventricle and right auricle) detected by 18 F-FDG PET-CT that allowed an early diagnosis and chemotherapy, therefore, improving the survival [9]. Synchronous lesions were detected in bilateral atria in our case, which were isodense and non-enhancing on CECT and therefore missed on CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement is usually revealed by cardiac complications and is associated with a poor prognosis. Julian et al reported two cases of DLBCL with cardiac involvement (apical septum, right ventricle and right auricle) detected by 18F-FDG that allowed an early diagnosis and chemotherapy, therefore, improving the survival [4]. Few cases of cardiac involvement in DLBCL have been reported, both primary and metastatic, detected by 18F-FDG [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…[7] In literature a few case reports have shown the pattern of involvement of metastatic involvement of the heart in non-Hodgkin's lymphoma. [89] We describe a unique case where FDG P et al lowed early diagnosis, prompt treatment and monitor response to chemotherapy of cardiac lesion, thus leading to the resolution of heart lesion before the occurrence of any cardiac complications.…”
Section: Case Reportmentioning
confidence: 99%